Protocol of the Nurses’ Mental Health Study (NMHS): a nationwide hospital multicentre prospective cohort study - Jiaxin Yang; Chongmei Huang; Shuiyuan Xiao; Xuting Li; Meng Ning; Zengyu Chen; Yusheng Tian; Qiang Yu; Yamin Chen; Ya-Min Li (BMJ Open)
Introduction Due to high workload, shift work and shortage of human resources, nurses are vulnerable to various mental health problems which are significantly related to their physical health, patient safety and healthcare quality. The long-term monitoring of nurses’ mental health and identifying its risk factors are necessary. Accounting for more than one-fifth of global nurses, Chinese nurses have a demanding healthcare workload, especially in tertiary hospitals, yet there is no national cohort concerning their mental health and associated factors. This study (Nurses’ Mental Health Study, NMHS) aims to investigate the mental health of Chinese nurses in tertiary hospitals and to identify the risk and protective factors.Methods and analysis NMHS is a multicentre prospective cohort study which plans to recruit at least 30 000 registered nurses from 62 tertiary hospitals using the cluster sampling method. Baseline data collection will be implemented through online questionnaires after obtaining informed consent from each participant. Variables including sociodemographic information, work-related factors, health status, lifestyle habits, objective experiences, family and social relations, current affairs opinions and overall evaluation will be collected. Annual follow-up will be conducted via a questionnaire link to monitor subsequent changes in nurses’ mental health and related factors.Patient and public involvement statement No patient and public involvement in the study design.Ethics and dissemination This study was approved by the Institute Review Board from the ethical committee of The Second Xiangya Hospital of Central South University (E20230048) and NMHS will be performed in line with Helsinki Declarations. The results of NMHS will inform nursing research and practice by providing evidence to nurse managers, healthcare organisations and the government about the target mental health outcomes for early prevention and intervention.Trial registration number This study has been registered at the Chinese Clinical Trail Registry (ID: ChiCTR2300072142, https://www.chictr.org.cn/showproj.html?proj=192676).